Ultrasonic evaluation of influence of hard acrylic resin denture on blood flow of mandibular denture supporting mucosa utilizing duplex color Doppler studies: An in vivo study - S Binsu; K Chandrasekharan Nair; Bijoy Jhon; Sanjna Nayar; Jose Julian; Muhammed Shahid (Wolters Kluwer Medknow Publications, 2017)
Aims: To determine the influence of hard acrylic denture base materials on the blood flow of mandibular denture supporting mucosa over a period of six months time. Materials and Methods: Select fifteen edentulous patients of age 55-75 years. The blood flow of the mandibular denture supporting mucosa was measured bilaterally in the molar region and in the incisor region utilizing Ultrasound colour Doppler (2D and Duplex Imaging). Measurements were performed prior to denture insertion and later after the dentures were worn for 1 month, 2 months, 3 months, 4 months, 5 months and 6 months. Statistical analysis used: Mean blood flow as measured by Ultrasound colour Doppler were tabulated significant changes if any at various time interval in comparison to baseline was assessed by Kruskalwallis ANOVA test followed by Wilkoxan sign rank test for pairwise comparison.( In the present study, P < 0.05 was considered as the level of significance). Results: The denture supporting mucosa exhibited a progressive reduction in the blood flow both with hard denture. The blood flow change with hard denture was a reversible condition as the blood flow improved at the end of six months. Kruskalwallis ANOVA test revealed no significant change in the blood flow at any interval of time in comparison to base value (P = 0.133). Conclusions: Within the limitations of the study denture supporting mucosa exhibited a progressive reduction in the blood flow with hard denture which was reversible.